Saxicolous Lichen biota of the Nevado Pastoruri (Áncash, Peru) - Ramírez, Ángel (2020)
The saxicolous lichens from Nevado Pastoruri (Cordillera Blanca, Department of Áncash) was evaluated at September month of years 2011 and 2012. We found 28 species, grouped into 19 genera and 14 families. The Families Lecanoraceae, Parmeliaceae and Teloschistaceae presented the greatest number of genera, while the genera Buellia, Lecanora and Umbilicaria recorded higher species richness. Crustacean lichens were dominant (61% of the total), followed by foliose (32%) and fruticose (7%).